99mTc-MDP Bone Scan and 18F-FDG PET/CT Imaging of Primary Hepatic Osteosarcoma - Liu, Yao; Tang, Wen; Huang, Zhongke (Nuklearmedizin - NuclearMedicine, 2023)
A 65-year-old man presented with abdominal bloating, pain, and nausea for 5 days. Abdominal CT revealed a heterogeneous mass with a large area of calcification, and rupture of the mass was seen around the capsulafibrosa. According to pathological examination after percutaneous puncture biopsy, the histopahological and immunohistochemical findings were suggestive of metastatic or primary hepatic osteosarcoma. Whole body bone scintigraphy demonstrated elevated 99mTc-MDP activity in hepatic mass, but no skeletal lesions. The diagnosis of primary hepatic osteosarcoma was finally confirmed. PET/CT showed hepatic mass with heterogeneous high-uptake, and multiple metastases in portacaval lymph nodes, lungs and the third thoracic vertebra were considered.
Keywords: 18F-FDG; 99mTc-MDP; primary hepatic osteosarcoma